Genomic catastrophe, the peritoneal cavity and ovarian cancer prevention. Issue 3 (18th April 2022) - Yoon, Ju Yoon; Chapel, David B; Goebel, Emily; Qian, Xiaohua; Mito, Jeffrey K; Horowitz, Neil S; Miron, Alexander; Soong, T Rinda; Xian, Wa; Crum, Christopher P
Abstract: The current theory of carcinogenesis for the deadliest of 'ovarian' cancers—high‐grade serous carcinoma (HGSC)—holds that the malignancy develops first in the fallopian tube and spreads to the ovaries, peritoneum, and/or regional lymph nodes. This is based primarily on the observation of early forms of serous neoplasia (serous tubal intraepithelial lesions [STILs], and serous tubal intraepithelial carcinomas [STICS]) in the fimbria of women undergoing risk reduction surgery. However, these lesions are uncommon in the general population, confer a low risk (5%) of HGSC following their removal in at‐risk women with germ‐line BRCA1/2 mutations, and require 4 or more years to recur as intraperitoneal HGSC. These features suggest that isolated STILs and STICs behave as precursors, with uncertain cancer risk rather than carcinomas. Their evolution to HGSC within, or after, escape from the tube could proceed stepwise with multiple biologic events; however, it is unclear whether tubal or ovarian HGSCs encountered in the setting of advanced disease evolved in the same fashion. The latter scenario could also be explained by a 'catastrophic' model in which STICs suddenly develop with invasive and metastatic potential, overwhelming or obscuring the site of origin. Moreover, a similar model might explain the sudden emergence of HGSC in the peritoneal cavity following escape of precursor cells years before. Long‐term follow‐up data from opportunistic or prophylactic salpingectomy should shed light on where malignant transformation occurs, as well as the timeline from precursor to metastatic HGSC. © 2022 The Pathological Society of Great Britain and Ireland.